Investigation of myocardial protection during pediatric CPB: Practical experience in 100 Chinese hospitals. (January 2022) - Zhang, Peiyao; Liu, Jinping; Tong, Yuanyuan; Guo, Shengwen; Bai, Liting; Jin, Yu; Feng, Zhengyi; Zhao, Ju; Li, Yixuan
Many measures have been proposed for myocardial protection in pediatric congenital heart surgeries, but little data is available for China. This study investigates myocardial protection strategies in pediatric cardiopulmonary bypass (CPB) throughout China. Online questionnaires were delivered to 100 hospitals in 27 provinces. The number of yearly on-pump pediatric cardiovascular surgeries in these hospitals varied greatly. About 91.0% of respondents believe that each surgery should have at least two perfusionists, while only 64.0% of hospitals actually met this requirement. For pediatric patients, crystalloid cardioplegia was more prevalent than blood-based cardioplegia. Histidine-tryptophan-ketoglutarate solution and St. Thomas crystalloid solution were dominant among crystalloid cardioplegia. Del Nido cardioplegia and St. Thomas blood-based cardioplegia ranked the top two in the popularity of blood-based cardioplegia. Dosages varied among different kinds of cardioplegia. In the choice of different cardioplegia, perfusionists mainly focused on myocardial protective effect and cost. Hypothermia of cardioplegia solution was maintained by ice buckets in 3/4 of the hospitals in this survey. In conclusion, the essence of myocardial protection management during pediatric CPB was cardiac arrest induced by cardioplegia under systemic hypothermia. However, there is no uniform standard for the type of cardioplegia, or dosages. Therefore, well-designed multicenter randomized controlled trials are warranted to provide tangible evidence for myocardial protection of cardioplegia in pediatric CPB.